THE APPLICABILITY OF INCLUSIVE EDUCATION IN PHYSICAL EDUCATION CLASSES. (Fiep Bulletin - online, 2024)
Introduction: Inclusive Education (IE) must be implemented in schools to educate students efficiently and with equal opportunities. The objective of this study was to investigate how IE has been carried out for students with physical disabilities (PWDs) in public schools in the municipality of Ananindeua – Pará. Methods: Information was collected via a semi-structured questionnaire. The samples were Physical Education and Special Education teachers, who directly serve these students in their respective schools to understand the difficulties, understandings and attitudes educators have on the topic. Results: The study was carried out with a sample of 53 teachers. The results showed that 81.1% of teachers have already had the opportunity to work in Ananindeua schools with PWDs, where 77.4% are currently serving this population in their classes. Participation adapted to all activities during classes is the most used by teachers (45.3%). When there is a PWDs, 75.5% of teachers promote inclusion; 17% promote Integration; and 0% exempt the student from classes. Regarding preparation to serve them: 45.3% say they are 70 to 90% prepared, but need continued training on the topic. As for school accessibility, 54.7% say it needs improvement in both the external and internal environment; 0% understand that accessibility is perfect. Conclusion: In general, Ananindeua teachers are aware and supportive of the process of including PWDs, but difficulties in accessibility, infrastructure and professional preparation still prevent better inclusive service for students with disabilities.
Keywords: 1. Physical Activity; Children with disabilities; Accessibility